POTENTIAL OF NOSTOC MUSCORUM FOR THE DECOLORIZATION OF TEXTILE DYE RGB-RED - SURBHI SINHA,; SUBHASHA NIGAM,; RACHANA SINGH, (International Journal of Pharma and Bio Sciences, 2015)
Nostoc muscorum, a dominant kind of cyanobacterial bloom was found as a viable biomass for decolorization of synthetic RGB-Red dye. Batch studies revealed the capacity of algal species in dye degradation which was dependent on initial pH (2-12), initial dye concentration (10 mg L-1 - 50 mg L-1), temperature (20 °C, 30 °C, 40 °C) and contact time (5 min-180 min). Maximum growth of algae was observed at 50 mg L-1 dye concentration. Optimal pH for maximum decolorization was determined at pH 3. The data obtained fitted well with Langmuir adsorption isotherm. This study confirmed the potential of blue green algae Nostoc muscorum to degrade textile dye, suggesting the possibility of its application in developing an oxidation pond system for textile effluent treatment at pilot scale study.